Investigation of quality sumisheutvorennya on performance diesel engine when operating on biodiesel and diesel fuel - Семенов, В.Г.; Васильєв, І.П.; Атамась, А.І. (Proceedings of National Aviation University (archive), 2009)
In the article it is considered the results of research of influence of quality are resulted formation of mixture indexes of diesel engine during work on biodiesel and diesel fuels.